POWDERY MILDEW DISEASE IN SOME NATURAL AND EXOTIC PLANTS OF ISTANBUL, TURKEY - (:unkn) unknown (PAKISTAN BOTANICAL SOC, 2012)
Powdery mildew is a disease that affects a wide range of plants and is caused by many different species of fungi. The disease is easy to diagnose since its symptoms are quite distinctive. Powdery mildew usually produces a white powdery substance that grows on both sides of the leaf surfaces. These leaves may become twisted, distorted, then wilt and die as a result of infection. Although humidity requirements for germination vary, all powdery mildew species can germinate and get infected in the absence of water. The powdery mildews seldom kill their hosts; the fungi reduce the amount of photosynthesis taking place, increase respiration and transpiration, and cause slower growth. This study was carried out between the years 2008 and 2010, and diseased plant samples were collected from urban lands, especially in parks, public and private gardens, road edges, medians and nurseries in 36 of 39 districts of Istanbul. In this study, 43 powdery mildew fungi species were observed and identified on 73 different plant species. Some of these fungi observed on a single plant species were Erysiphe convolvuli var. convolvuli, E. flexuosa, E. lagerstroemiae, E. platani, E. sparsa, E. syringae, E. trina, E. viburni, Leveillula taurica, Microsphaera alni var. vaccinii, M. alphitoides, M. berberidicola, M. diffusa, M. grossulariae, M. platani, M. quercina, Oidium sp., O. begonia, O. euonymi-japonica, O. lauraceum, O. lini, Peronospora erodii, guttata, Sphaerotheca fusca, S. humuli, S. lanestris, S. macularis, S. pannosa var. rosae, Uncinila aceris, U. circinata, U. clintonii, U. geniculata, U. necator, U. Parvula and U. salicis. Some powdery mildew fungi were cosmopolitan and showed parasitic features for many different plant species. These fungi are Microsphaera alni (11 plant species), Erysiphe polygoni (9 plant species), Erysiphe cichoracearum and Phyllactinia cotylea (8 plant species).
Keywords: ECOLOGICAL CHARACTERISTICS; CHROMOSOMAL LOCATION; UNCINULA-NECATOR; RESISTANCE; FLORA; WHEAT; GENE; AMPELOMYCES; DISTRICT; SIDE